Antropofagia cultural brasileira e as práticas inventivas de Hélio Oiticica, Paulo Freire e Augusto Boal: contribuições ecologistas e interculturais para a formação de professores(as) - Silva, Ivete Souza da (2013)
The present research that I bring as Doctoral Thesis in Education in the Knowledge Training and Professional Development (PPGE-UFSM), has as objective to contribute with theoretical and epistemological aids for Teacher Training in general, and particularly for Environmental Education (EA), from the anthropophagical assumptions and the inventive practices of Hélio Oiticica, Paulo Freire and Augusto Boal, in an intercultural perspective of education. The framework that guided the researcher´s investigative and reflexive eye (BARCELOS, 2005, 2006) in the sense of the research information production (JAQUES GAUTHIER, 1998), was of establishment of dialogues that favor the intercultural aspects (CANCLINI, 2003b) with imaginaries and representations about environmental issues in general and particularly teacher training, present in productions of cultural anthropophagical orientation, after the Modern Art Week of 1922, selected for this research and the inventive practices of Hélio Oiticica, Augusto Boal and Paulo Freire. When trying to define the method of this research I affirm that it is a qualitative research and has predominantly theoretical-bibliographical characteristics, while bringing in its design the intention to investigate the process of incorporation of the theoretical references in my formation process. In this sense, an autobiographical aspect is added as I tell about the devouring I did while on this anthropophagical road, bringing the educational propositions that I have constructed: Parangolé, Anthropophagical Bed and Collective Panel. Such propositions consisted of interventions in different educational settings and had as intention to construct provocative spaces for reflection, aiming to unsettle ideas and crystallized practices that, as plant elites in communication with the soil (ANDRADE, 1924), we cultivate in our teaching. The anthropophagical assumptions and the inventive practices of the authors researched here have contributed with teacher training in general, and particularly with Environmental Education, as they suggest the construction of educational practices where the student is no longer only a spectator, but becomes the protagonist in the educational process. Such proposition is present in the ideas of participation, creation and dialogue brought by the authors (OITICICA, 2008; BOAL, 1975; FREIRE)